A intenção de uso do consumidor brasileiro em relação ao carro elétrico - Monteiro , Daniel Braga (2017)
The introduction of new products, such as the electric car, has a great potential of failure, since it represents a different proposal for consumers when compared to combustion vehicles. This study used the Decomposed Theory of Planned Behavior - DTPB (Taylor and Todd, 1995) to investigate the Brazilian’s consumer intended use of the electric car. The issue of research that formed the North for this study is: what is the intention of the Brazilian consumer in relation to the use of the electric car? The final sample of this quantitative research indicated 383 valid respondents and the main result obtained from this study was the great influence exerted by the construct Attitude concerning the intended use, which goes against the important study of Venkatesh et al. (2003). On the other hand, Attitude is substantially influenced by the Relative Advantage and Compatibility when it comes to the electric car issue. In other words, it is important that consumers perceive this innovation as advantageous, superior to combustion vehicles, and even that this should be compatible with their values and their personal beliefs.